Subjective well-Being pada remaja dari keluarga broken home - Astuti, Mis. Yuli, Dr. Nisa Rachmah N.A., M.Si., Psi (2015)
This research purposes to know factors influence subjective well-being of adolescent, and how is condition subjective well-being of adolescent from broken home family. This research is qualitative with phenomenology research method. Subject of this research is 3 students of SMP Negeri 1 of Eromoko, Wonogiri regency has characteristic: 1) children come from broken home family 2) 12 years old to 16 years old. Collecting data uses interview and observation. Analysis procedure of data is open coding, axial coding and selective coding. Base on analysis result of data can conclusion factors influence subjective well-being of informant is social support, care pattern of parent, gender, economic, copying strategic subjective well-being of informants Vn and DN are high, while informant An is low. Behavior condition subjective well-being base on life satisfaction aspect has some moments like graduate elementary value is good who gets bicycle. Positive effect moment is recreation with family, helping family, sport winner is good category. Negative effect is wrong thinking and he feels to be load, he has not money pocket to school, negative thinking to father and neighborhood, he is sad when remember father, get bad value, grand ma and grand pa from father were death, mother angry with him, jealous with friends. Keyword: Subjective well-being; broken home, SMP N 1 Eromoko